Factors associated with dental pain related to last dental visit among adult patients - Nazir, Muhammad Ashraf (Dental and medical problems, 2018)
Most dental visits are made to seek dental care to relieve dental pain. However, the factors associated with behavior regarding dental visits due to pain are not fully understood. The objective of this study was to assess the factors associated with dental pain related to last dental visit among adults. The data was obtained from a cross-sectional study conducted on adults, aged 18-69 years, who visited public and private dental clinics in Dammam, Saudi Arabia. A pilot-tested, self-administered questionnaire was employed for data collection. Dental pain related to last dental visit was a dependent variable in the study. Gender, age, nationality, income and education levels, time since last dental attendance, type of dental clinic visited, and chronic systemic disease were important independent variables. The Pearson's χ2 test and multiple logistic regression analysis were used. The participants returned 671 questionnaires. Most of the participants were females (75.4%), and the majority (68.0%) attended private dental clinics. The prevalence of dental pain as the reason of last dental visit was 70.4%. A logistic regression model showed that odds ratio for subjects who visited the dentist due to pain in ≤1 year was 0.34 (95% CI = 0.24, 0.49) compared with patients who visited the dentist in >1 year. Similarly, male gender (OR = 0.64; 95% CI = 0.42, 0.97) subjects aged ≤35 years (OR = 0.61; 95% CI = 0.40, 0.95) were less likely to make pain-related dental appointments than females and individuals over 35 years. The respondents who attended private dental clinics were 1.56 (95% CI = 1.12, 2.37) times more likely to visit the dentist because of pain than those who attended a public clinic. Delayed dental visits, female gender, age over 35 years, and private clinic attendance were significant factors associated with dental consultations motivated by pain.